Ultrasound Neuromodulation as a New Brain Therapy - Roland Beisteiner; Mark Hallett; Andres M. Lozano (Advanced Science)
Abstract Within the last decade, ultrasound has been “rediscovered” as a technique for brain therapies. Modern technologies allow focusing ultrasound through the human skull for highly focal tissue ablation, clinical neuromodulatory brain stimulation, and targeted focal blood‐brain‐barrier opening. This article gives an overview on the state‐of‐the‐art of the most recent application: ultrasound neuromodulation as a new brain therapy. Although research centers have existed for decades, the first treatment centers were not established until 2020, and clinical applications are spreading rapidly.